Authoritarian resilience and democratic representation in Morocco: Royal interference and political parties' leaderships since the 2016 elections. Issue 2 (14th March 2020) - Desrues, Thierry
ABSTRACT: After the 'Arab Spring' and the second electoral victory of the Islamist party of Justice and Development in 2016, Moroccan King Mohammed VI had to find new ways to reduce the uncertainty of transparent elections and, as a result, his loss of control over the winner of the House of Representatives elections and the choice of the Head of Government. This profile will analyse a few of the paradoxical implications of the 2011 constitutional reform and the royal narrative for democratic transition, and how these have impacted the political practice of the relevant actors. More precisely, the profile will attempt to clarify the various accommodations by both the King and the political parties, to contextualize the reform and better understand the persistence of authoritarian features despite the democratic hybridization of the Moroccan political system.